GEORGIA: ATURAL ENERGY RESOURCES - CHOMAKHIDZE, Demur (CENTRAL ASIA AND THE CAUCASUS, 2007)
This article examines Georgia’s natural fuel and energy resources (FER), both conventional (hydropower, oil, gas, coal) and non-conventional (alternative). Special attention is paid to hydropower and to alternative energy sources. The author assesses the current level of their development in the republic. Generally speaking, Georgia is not very rich in FER, but almost all kinds of these resources are found in its territory in greater or lesser amounts. Despite its limited reserves of fossil fuel, the republic cannot be regarded as a region poor in energy resources in general, because its rivers hold huge amounts of hydropower, largely compensating for the fuel shortage in the country. Another reason is that Georgia is rich in alternative energy sources (sun, thermal waters, wind, etc.). An approximate structure of the country’s conventional FER is presented in Fig. 1, which shows that hydropower makes up the main part of both potential (theoretical) resources and proven (established balance) reserves (64.1% and 80.8%, respectively). Altogether, potential resources add up to 6.4 billion tons of oil equivalent (toe), and established balance reserves, to 2.6 billion toe. These energy resources (together with alternative resources) constitute Georgia’s total energy potential, which should basically ensure the development of the republic’s energy sector.Nevertheless, the FER development level in Georgia is currently very low